2004
DOI: 10.1073/pnas.0406788101
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the fibroblast growth factor system in major depression

Abstract: In this report we describe findings that imply dysregulation of several fibroblast growth factor (FGF) system transcripts in frontal cortical regions of brains from human subjects with major depressive disorder (MDD). This altered gene expression was discovered by microarray analysis of frontal cortical tissue from MDD, bipolar, and nonpsychiatric control subjects and was verified by quantitative real-time PCR analysis and, importantly, in a separate cohort of MDD subjects. Furthermore, we show, through a sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
272
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(288 citation statements)
references
References 40 publications
12
272
2
1
Order By: Relevance
“…36,37,58,59 Few studies have explored global expression changes between groups of suicides and psychiatrically normal controls, some have however focused on a particular psychiatric diagnosis, such as bipolar disorder or schizophrenia, and included within these groups subjects that died by suicide. [60][61][62][63][64][65][66][67] Sibille et al 51 recently compared expression patterns in BA9 and BA47 of depressed suicides versus psychiatrically normal controls matched on the basis of sex, age, DAVID genes correspond to the total number of unique DAVID annotated genes. The percentage represents the number of differentially expressed genes belonging to a given category over the total number of DAVID annotated genes.…”
Section: Discussionmentioning
confidence: 99%
“…36,37,58,59 Few studies have explored global expression changes between groups of suicides and psychiatrically normal controls, some have however focused on a particular psychiatric diagnosis, such as bipolar disorder or schizophrenia, and included within these groups subjects that died by suicide. [60][61][62][63][64][65][66][67] Sibille et al 51 recently compared expression patterns in BA9 and BA47 of depressed suicides versus psychiatrically normal controls matched on the basis of sex, age, DAVID genes correspond to the total number of unique DAVID annotated genes. The percentage represents the number of differentially expressed genes belonging to a given category over the total number of DAVID annotated genes.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Various microarray profiles in mood disorder have been reported that use different microarray platforms, analysis methodology, regional differences, agonal factors and brain pH. [4][5][6][7][8][9][10][11][12][13][14] Presumably, a substantial heterogeneity in the pathophysiology of mood disorder coupled with small sample sizes and small fold changes contributes to the lack of consistency among the findings. 15 In five microarray studies a broad mitochondrial dysfunction was reported in neuropsychiatric disorders.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…13,33 Microarray data analysis Cohort composition for microarray analysis-A control group analysis was conducted by splitting the controls into subgroups at a median pH of 6.87 and comparing the gene expression profile with PLMfit. This analysis was used to evaluate gene expression results for agonal-pH sensitive genes.…”
Section: Oligonucleotide Microarraysmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, FGF ligand/FGF ligand and FGFR1/FGFR1 dimerization may expand the spectrum of interactions between FGFs and FGFR affecting their binding and signaling properties [5]. Anomalous FGF signaling is associated with several human diseases, for instance uncontrolled FGF signaling has been linked to the etiology of neurodegenerative disorders, such as major depressive disorder and Parkinson's disease [6].…”
Section: Introductionmentioning
confidence: 99%